PENGARUH KINERJA KEUANGAN DAN EARNING PER SHARE DENGAN KURS US DOLAR TERHADAP RUPIAH SEBAGAI VARIABEL INTERVENING TEHADDAP HARGA SAHAM PT. UNILEVER INDONESIA Tbk. TAHUN 2006-2024 - Tjahjo Nugroho, Judianto; Dyasinta Afrilla, Eka; Sitanggang, Milesren (Sekolah Tinggi Ilmu Ekonomi GICI, 2024)
This study aims to determine the effect of company's financial performance and earning per share on stock price with US Dollar rate exchange against agains Rupiah as the intervening variable. The study used a quantitative approach with the type of causal associative research. The Data used is the financial data of PT Unilever Indonesia Tbk for the period 2006 to 2023 and data from Bank Indonesia. The data analysis in this study used Partial Least Square – Structural Equation Modeling (PLS – SEM) with STATCAL software updated March 7, 2024. The results showed that earning per share significantly affect stock price directly, but there is no significant variable that affects stock price through with US Dollar rate exchange against agains Rupiah.